Synthesis and Controlled Release of Vitamin C Intercalated Zn/Al Layered Double Hydroxide - Gao, Xiaorui; Lei, Lixu; Chen, Le; Wang, Yuqiao; He, Leqin; Lian, Yiwei (Asian Journal of Chemistry, 2014)
A drug-inorganic composite involving vitamin C intercalated in Zn-Al layered double hydroxides has been synthesized by a coprecipitation method. Powder X-ray diffraction, fourier transform infrared, elemental analysis, thermogravimetric analysis and UV-visible absorption spectroscopy indicate a successful intercalation of vitamin C into the interlayer galleries of the layered double hydroxides host and the loading of vitamin C in the layered double hydroxides is 84 %. Studies of vitamin C release from the layered double hydroxides in deionized water and in aqueous CO32- solutions imply that Zn2Al-vitamin-C layered double hydroxides is a better controlled release system. Analysis of the release profiles using a number of kinetic models suggests a solution-dependent release mechanism and a combination process of diffusion-controlled and ion exchange deintercalation mechanisms in deionised water, but an ion exchange process in CO32- solution.